Headache cessation by an educational intervention in grammar schools: a cluster randomized trial. (22nd September 2014) - Albers, L.; Heinen, F.; Landgraf, M.; Straube, A.; Blum, B.; Filippopulos, F.; Lehmann, S.; Mansmann, U.; Berger, U.; Akboga, Y.; von Kries, R.
<x xml:space="preserve">Abstract</x> Background and purpose Headache is a common health problem in adolescents. There are a number of risk factors for headache in adolescents that are amenable to intervention. The aim of the study was to assess the effectiveness of a low‐level headache prevention programme in the classroom setting to prevent these risk factors. Methods In all, 1674 students in 8th–10th grade at 12 grammar schools in greater Munich, Germany, were cluster randomized into intervention and control groups. A standardized 60‐min prevention lesson focusing on preventable risk factors for headache (physical inactivity, coffee consumption, alcohol consumption and smoking) and providing instructions on stress management and neck and shoulder muscle relaxation exercises was given in a classroom setting. Seven months later, students were reassessed. The main outcome parameter was headache cessation. Logistic regression models with random effects for cluster and adjustment for baseline risk factors were calculated. Results Nine hundred students (intervention group N = 450, control group N = 450) with headache at baseline and complete data for headache and confounders were included in the analysis. Headache cessation was observed in 9.78% of the control group compared with 16.22% in the intervention group (number needed to treat = 16). Accounting for cluster effects and confounders, the probability of headache cessation in the intervention group was 1.77 (95% confidence interval = [1.08; 2.90]) higher than in the control group. The effect was most pronounced in adolescents with tension‐type headache: odds ratio = 2.11 (95% confidence interval = [1.15; 3.80]). Conclusion Our study demonstrates the effectiveness of a one‐time, classroom‐based headache prevention programme.